Acaricidal and insecticidal activities of essential oils of Cinnamomum zeylanicum barks cultivated from France and India against Dermatophagoides spp., Tyrophagus putrescentiae and Ricania sp - Jeon, Ye-Jin; Lee, Sang-Guei; Lee, Hoi-Seon (Applied biological chemistry, 2017)
The chemical composition of Cinnamomum zeylanicum bark oils cultivated from France and India was analyzed by GC–MS. The main components of C. zeylanicum oil were cinnamaldehyde (63.97 and 67.21%) and eugenol (6.84 and 19.79%) from France and India, respectively. Acaricidal and insecticidal activities of C. zeylanicum oils against Dermatophagoides sp, T. putrescentiae and Ricania sp. were evident. The LC 50 values of C. zeylanicum oil were 123.77 and 93.06 mg/L in samples from France and India, respectively, against Ricania sp. adults in the spray bioassay. Using the leaf-dipping bioassay, the LC 50 values of the oil from France and India were 80.99 and 57.44 mg/L, respectively, against Ricania sp. nymphs. Acaricidal activity of the C. zeylanicum oil from India in the fabric disk bioassay (LD 50 , 0.64, 0.51 and 1.72 μg/cm 3 , respectively) was greater than France oil (LD 50 , 0.92, 0.81 and 1.82 μg/cm 3 , respectively). In the filter paper bioassay, india oil (LD 50 , 1.82, 1.55 and 3.08 μg/cm 2 , respectively) was more potent than France oil (LD 50 , 2.07, 1.94 and 6.20 μg/cm 2 , respectively) against D. farinae , D. pteronyssinus and T. putrescentiae . The results indicate that the essential oils of C. zeylanicum barks could be an effective natural acaricide and insecticide for controlling house dust mites, stored food mites and fruit pests.